Patterns of Fungal Community Assembly Across Two Culex Mosquito Species - Tawidian, Patil; Jumpponen, Ari; Michel, Kristin (Frontiers in Ecology and Evolution, 2022)
In the aquatic environment, mosquito larvae encounter bacteria and fungi that assemble into bacterial and fungal communities. The composition and impact of mosquito-associated bacterial community has been reported across larvae of various mosquito species. However, knowledge on the composition of mosquito-associated fungal communities and the drivers of their assembly remain largely unclear, particularly across mosquito species. In this study, we used high throughput sequencing of the fungal Internal transcribed spacer 2 (ITS2) metabarcode marker to identify fungal operational taxonomic units (OTUs) and amplicon sequence variants (ASVs) associated with field-collected Culex restuans and Culex pipiens larvae and their breeding water. Our analyses identified diverse fungal communities across larval breeding sites collected on a fine geographic scale. Our data show that the larval breeding site is the major determinant of fungal community assembly in these mosquito species. We also identified distinct fungal communities in guts and carcasses within each species. However, these tissue-specific patterns were less evident in Cx. restuans than in Cx. pipiens larvae. The broad ecological patterns of fungal community assembly in mosquito larvae did not vary between OTU and ASV analyses. Together, this study provides the first insight into the fungal community composition and diversity in field collected Cx. restuans and Cx. pipiens larvae using OTUs and ASVs. While these findings largely recapitulate our previous analyses in Aedes albopictus larvae, we report minor differences in tissue-specific fungal community assembly in Cx. restuans larvae. Our results suggest that while the fungal community assembly in mosquito larvae may be generalized across mosquito species, variation in larval feeding behavior may impact fungal community assembly in the guts of mosquito larvae.